(untitled) (International Journal of Engineering and Computer Science, 2016)
This paper presents the basic idea of speech recognition and its progress till date. Speech recognition is essential for a communication between human and machine.The ultimate goal of the technology is to able to produce a system that can recognize with 90-100% accuracy all words that are spoken by any user in different language .This paper helps in selecting the techniques along with their relative advantage and disadvantage. Under the speech recognition using e-speaking product,we create a small and efficient program to take humans voice as input and convert it into keyboard ,mouse system and program events and even speak to you to let you know what it has performed.